Attitude of form two students towards learning science in english: A case study of schools in Kota Samarahan / Caesar De Alwis … [et al.] - De Alwis, Caesar; Joe, Saira; Wan Kahar, Sharifah Aisyah (2004)
This report presents the findings of a research project, which examined the attitude of Form Two students towards learning Science in English. The research was both quantitative and qualitative. A total of 320 students from six secondary schools in Kota Samarahan District in the Samarahan Division participated in this research. The students had to complete one set of questionnaire, which consisted of 40 items using the Likert scale. The questionnaire was divided into two sections: attitude towards English Language and attitude towards learning Science in English. The items were grouped into four Dimensions for each section, namely; English Language Dimension, Language -Related Dimension, Job/Future Study Dimension and Cultural Dimension. The items in the second section were also grouped into four similar Dimensions namely; Science Dimension, Science-Related Dimension, Job/Future Study Dimension and Cultural Dimension.